2020
DOI: 10.3390/ijms21062223
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Rice Long-Chain Acyl-CoA Synthetase 9 (OsLACS9) in the Chloroplast Envelope Membrane

Abstract: The long-chain acyl-CoA synthetases (LACSs) are involved in lipid synthesis, fatty acid catabolism, and the transport of fatty acids between subcellular compartments. These enzymes catalyze the critical reaction of fatty acyl chains to fatty acyl-CoAs for the triacylglycerol biosynthesis used as carbon and energy reserves. In Arabidopsis, LACSs are encoded by a family of nine genes, with LACS9 being the only member located in the chloroplast envelope membrane. However, the comprehensive role of LACS9 and its c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…9 ). In addition, there were signatures of selection for Long-Chain Acyl-CoA Synthetase ( LCAS ), a gene known for affecting storage oil synthesis and plant height 26 28 , and transcriptome analysis showed differential expression in different tissues (Supplementary Fig. 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…9 ). In addition, there were signatures of selection for Long-Chain Acyl-CoA Synthetase ( LCAS ), a gene known for affecting storage oil synthesis and plant height 26 28 , and transcriptome analysis showed differential expression in different tissues (Supplementary Fig. 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…Plastids are the places where de novo synthesis of FAs occurs. Several LACS orthologs are known to localize to the plastid envelope ( Figure 2 ), including AtLACS9, HaLACS1 from sunflower ( H. annuus ), and OsLACS9 from rice ( Oryza sativa ) ( Schnurr et al, 2002 ; Aznar-Moreno et al, 2014 ; Jessen et al, 2015 ; Kitajima-Koga et al, 2020 ). They are implicated to function in the activation of de novo synthesized LCFAs in plastids.…”
Section: Subcellular Localizationmentioning
confidence: 99%
“…Breuers et al further research demonstrated the localization of AtLACS9 to the outer envelope membrane [ 41 ]. In rice, the OsLACS9 was located in the chloroplast envelope membrane [ 42 ]. In this study, subcellular localization analysis indicated that the fluorescence signal of the BnLACS9-GFP fusion protein was around the chloroplast but did not overlap with the spontaneous fluorescence signal of the chloroplast and even formed loop structures and thin tubules from the chloroplast (Fig.…”
Section: Discussionmentioning
confidence: 99%